2003
DOI: 10.1200/jco.2003.04.093
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Exercise Training in Postmenopausal Breast Cancer Survivors: Cardiopulmonary and Quality of Life Outcomes

Abstract: Exercise training had beneficial effects on cardiopulmonary function and QOL in postmenopausal breast cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

58
581
7
25

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 664 publications
(671 citation statements)
references
References 35 publications
58
581
7
25
Order By: Relevance
“…Quality of life is a multidimensional construct including physical and psychosocial dimensions [1]. Studies on the effect of physical training in cancer survivors suggest that physical training is primarily associated with improved physical and functional aspects of quality of life, rather than the social and emotional domains [7,8,14]. A recent meta-analysis reported that cognitive-behavioral therapy had positive effects on mental health of cancer survivors [26].…”
Section: Introductionmentioning
confidence: 99%
“…Quality of life is a multidimensional construct including physical and psychosocial dimensions [1]. Studies on the effect of physical training in cancer survivors suggest that physical training is primarily associated with improved physical and functional aspects of quality of life, rather than the social and emotional domains [7,8,14]. A recent meta-analysis reported that cognitive-behavioral therapy had positive effects on mental health of cancer survivors [26].…”
Section: Introductionmentioning
confidence: 99%
“…Several of these programs were offered to individuals in group format and these reported improvement in quality of life, physical functioning and fatigue in cancer patients during primary treatment [3][4][5][6][7][8][9][10] and after completion of initial treatment [11][12][13][14]. Recently, interest has been growing in patients' experience with training within groups.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies investigated the effect of exercise in cancer survivors. Both studies used fatigue as a secondary outcome and showed beneficial effects (Courneya et al, 2003;Pinto et al, 2005). The fifth study found that acupuncture was a more effective method to improve fatigue compared with acupressure or sham acupressure (Molassiotis et al, in press).…”
mentioning
confidence: 99%